Effects of Supplemental Leucine on Growth, Nutrient Use, and Muscle and Visceral Tissue Mass in Holstein Bull Calves Fed Milk Replacer - Reiners, Jessica N.; Steele, Michael A.; Vonnahme, Kimberly A.; Maddock Carlin, Kasey R.; Swanson, Kendall C. (Frontiers in Animal Science, 2022)
To determine the effects of leucine supplementation on body weight (BW), tissue mass, nutrient digestibility, concentration of serum amino acids (AA) and metabolites, and protein abundance of elongation initiation factor 4E (eIF4E) in skeletal muscle, 23 Holstein bull calves (43.3 ± 1.16 kg; 11.3 ± 0.57 days of age) fed milk replacer at 2.5% of body weight (BW; dry matter basis) were used in a randomized complete block design. Leucine was supplemented at 0, 0.4, 0.6, or 0.8 g Leu/kg body weight (BW) per day for 28 d. Data were analyzed using the MIXED procedure of SAS. Leucine supplementation did not affect calf BW (P = 0.73), and digestibility of nitrogen (P = 0.21), organic matter (P = 0.28), and dry matter (P = 0.28). Masses proportional to BW of the pancreas (P = 0.04), omasum (P < 0.01), and spleen (P = 0.01) were quadratically affected by treatment where tissue mass decreased at 0.4 g Leu/kg BW and increased at 0.6 and 0.8 g Leu/kg BW. Semitendinosus mass proportional to BW tended (P = 0.07) to be quadratically affected, as tissue mass increased at 0.4 g Leu/kg BW, and decreased at 0.6 and 0.8 g Leu/kg BW. Serum Leu concentration increased linearly (P = 0.002; day × time × treatment) across days and after feedings with increased supplemental Leu. Increasing supplemental Leu linearly decreased serum Ala (P < 0.01), Arg (P = 0.04), Ile (P = 0.02), Met (P < 0.01), and Pro (P = 0.05) concentrations, and quadratically affected serum Glu (P = 0.04) and Lys (P = 0.03) concentrations where serum Glu and Lys concentrations were decreased at 0.4 g Leu/kg BW and increased at 0.6 and 0.8 g Leu/kg BW. There was no effect of treatment on protein abundance of eIF4E in semitendinosus or longissimus dorsi. These data indicate that supplemental Leu did not influence ADG and nitrogen retention in calves fed milk replacer. However, changes in serum AA concentrations and tissue masses proportional to BW suggest that supplementation of Leu at lower levels could increase the use of AA for non-visceral tissue growth.